(untitled) (KIUT Publication, 2025)
This article analyzes macroeconomic and microeconomic risks arising in the context of sustainable economic development and develops effective management mechanisms for them. Considering the ecological, social, and financial aspects of economic growth, tools for identifying, assessing, and minimizing risks are examined based on a systematic approach. Recommendations are proposed based on modern risk management practices and international experience to ensure the stability and resilience of the national economy.